The Influence of Perceived Risk and Consumer Knowledge on Behavior Intention with Consumer Trust As an Intervening Variable in Life Insurance Products in Balikpapan and Makassar - Ani Sri Winarti; Herning Indriastuti; Imron Sohsan (CV. Publikasi Indonesia, 2023)
Life insurance is a financial product that protects individuals from the risk of unfortunate events such as death and disability. Although the life insurance market is showing increased penetration, many still do not have life insurances. Purpose: This research aimed to analyze the influence of consumer trust in the relationship between the relationship of perceived risk and consumer knowledge with behavior intention. Design/methodology/approach: This research used a quantitative approach. The research was conducted on 210 respondents in Makassar and Balikpapan. Data were collected through an online questionnaire. The data collected were analyzed using the Structural Equation Modelling (SEM) with the AMOS application. Findings: Perceived Risk: financial risk, performance risk, physical risk, social risk and overall risk have negative influences and not significant to behavior intention. Consumer knowledge have a positive influence and significant to behavior intention. Consumer trust was a variable that mediated the influence of perceived risk and consumer knowledge on behavior intention.